2011
DOI: 10.1158/1055-9965.epi-11-0753
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Sex Steroids and Risk of Cervical Carcinoma: Results from the EPIC Study

Abstract: Background: Epidemiologic data and animal models suggest that, despite the predominant role of human papillomavirus infection, sex steroid hormones are also involved in the etiology of invasive cervical carcinoma (ICC).Methods: Ninety-nine ICC cases, 121 cervical intraepithelial neoplasia grade 3 (CIN3) cases and 2 control women matched with each case for center, age, menopausal status and blood collection-related variables, were identified in the European Prospective Investigation into Cancer and Nutrition (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…Aminoestrol lacks the substituent alkyl-alcohol on the amino group, the change of -NH 2 in this molecule for the -OH in C17 of E 2 produces a drop of its estrogenic properties in vivo and in vitro models, and confers to this steroid an increase of selectivity for the ERb interaction [24]. In this regard, the role of estrogens on the ERa in human cervical cancer has been well documented [25] and therefore the main effect of aminoestrol on the ERb may diminish deleterious consequences on the reproductive system, representing an advantage to HRT.…”
Section: Discussionmentioning
confidence: 99%
“…Aminoestrol lacks the substituent alkyl-alcohol on the amino group, the change of -NH 2 in this molecule for the -OH in C17 of E 2 produces a drop of its estrogenic properties in vivo and in vitro models, and confers to this steroid an increase of selectivity for the ERb interaction [24]. In this regard, the role of estrogens on the ERa in human cervical cancer has been well documented [25] and therefore the main effect of aminoestrol on the ERb may diminish deleterious consequences on the reproductive system, representing an advantage to HRT.…”
Section: Discussionmentioning
confidence: 99%
“…Although carcinogenicity of HPV infections is well established (21), the relationship between cervical cancer and testosterone is unclear. In premenopausal women, free, but not total, testosterone was associated with a greater risk of invasive cervical carcinoma, while among postmenopausal women, a positive association was observed for total, but not free, testosterone (92). How these observations apply to transmen is not known.…”
Section: Possible Effects Of Cross-sex Hormonesmentioning
confidence: 99%
“…The influence of estrogen levels in blood plasma on cervical carcinogenesis has also been evaluated in case-control studies [32,33]. The prolonged treatment of post-menopausal women with estradiol-progestin has been accompanied by an increased occurrence of cervical adenocarcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of women with invasive cervical carcinoma and cervical intraepithelial neoplasia grade 3, Rinaldi et al in 2011 suggested a role for testosterone and possibly E2 in invasive cervical carcinoma [33].…”
Section: Resultsmentioning
confidence: 99%